A Proposed Approach ‎for Effort‎ Estimation of Developing Mobile Applications - Karim Sayed Roshdi; Ezzat Samy Elbagoury (International Journal of Computers and Informatics, 2023)
Effort estimation techniques play a key role in the planning process for the development of mobile phone applications. The development of mobile applications is different from the traditional applications of information systems because of their dissimilar characteristics and the rapid advancement of technology used in the development of the former. For this, existing traditional effort estimation techniques may not be suitable for use in predicting the development effort of mobile applications. The process of estimating and predicting the effort depends mainly on the characteristics of the applications. The aim of this study is to propose a methodology for the use of intelligent techniques to predict the effort to develop mobile applications, which are considered unconventional, and to cope with the rapid development of the mobile application development environment.
Keywords: Effort Estimation; Mobile Application; Mobile Computing; Systematic Review